KEMBALI KE YANG ALAMI : Tawaran Keluarga Berencana Alamiah - Nadeak, Largus (LOGOS, 2003)
Family is a basis of social life in transforming and improving the values of life. Being a good family depends on how the family is planned. When we speak about a family planning, we touch a responsible and happy family. A family must plan the number of its member. And it demands right means. Nowadays, the means of family planning often used are artificial. These means have inclination to despise the organ of human procreation.Catholic Church suggests us to use natural family planning. This method respects natural riches of creation. The effectivity of this method depends on one’s ability to understand the phenomena of the organ of human procreation. For most families, it is not easy to understand these phenomena and the method of natural family planning. Therefore, though not appropriate to the traditional norm, KWI (Indonesian Bishop’s Conference) gives a possibility, that if a family has difficulty using natural family planning, this family can use alternative unabortive and permanent sterilisation means beside natural family planning. This idea is not contradict with natural family planning, but really in promotion of natural family planning.